ANALISIS FAKTOR â FAKTOR YANG MEMPENGARUHI AUDIT DELAY Periode 2008 - 2010 - Julius Chandra Hermanto, 08.05.52.0070; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2012)
This study is a study that examined the effect of corporate financial reporting to the audit delay. Audit delay is generally defined length of time the completion of the audit as measured from the date of closing of the financial year until the date of signing the audit report.In this study, the samples used by 92 companies from theÂ  manufacturing companies listed on the Indonesia Stock Exchange in the year 2008 to 2010 with a purposive sampling method. To analyze the hypothesis used multiple regression analysis.These results indicate that the size of the Profitability, Company Size Auditor Opinion, and Firm Size showed a significant effect on audit delay.Keywords: Audit Delay, Profitability, Company Size, Auditors Opinion, and Firm Size.